The art of drawing poses for beginners - Goldman, Ken, 1957-; Goldman, Stephanie (Walter Foster, 2022)
The Art of Drawing Poses for Beginners combines step-by-step pencil lessons and additional graphite portrait examples to demonstrate how to accurately render the human form in a variety of realistic poses.